Global Perspectives on Women in Combat Sports
XVI, 322 p.
Keywords: This volume offers a wide-reaching overview of current academic research on women's participation in combat sports within a range of different national and trans-national contexts, detailing many of the struggles and opportunities experienced by women at various levels of engagement within sports such as boxing, wrestling, and mixed martial arts.